KETERKAITAN UKURAN ORGANISASI DAN PEMAHAMAN MANAJEMEN TERHADAP PENERAPAN AKUNTANSI HIJAU (GREEN ACCOUNTING) - Muhammad Hasyim Ashari; Umi Muawanah; Oyong Lisa (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2020)
It is necessary to apply green accounting to public hospitals based on financial, social and environmental activities, as a form of economic responsibility (profit), social responsibility (people), and environmental responsibility (planet). The purpose of this study was to analyze and determine the effect of organizational size and management understanding of green accounting, either partially or simultaneously on the implementation of green accounting in public hospitals in Malang Raya, as well as the percentage level of the influence of these two variables on the implementation of green accounting in public hospitals in Malang Raya. This research is a quantitative study with a correlational approach. The population of 40 public hospitals spread across Malang District, Malang City, and Batu City. The sampling method uses probability sampling and snowball sampling. The sample used as many as 35 public hospitals. Data collection using a survey questionnaire using a 7 point likert scale. The novelty in this research is the implementation of green accounting based on economic responsibility, social responsibility, and environmental responsibility, using organizational size variables by considering public hospitals have different types, and using management understanding variables about green accounting. The results showed that the size of the organization and management's understanding of green accounting influence the implementation of green accounting in public hospitals in Malang Raya either partially or simultaneously. The influence of organizational size and management's understanding of green accounting on the implementation of green accounting is 33,9 %, and the remaining 66,1 % is influenced by other variables besides the two variables.